HYDROBIOLOGICAL STATUS OF A LESSER IDMALAYAN RIVER - Mohan, Madan (Journal of Indian Fisheries Association, 2015)
It is generally observed that a variety of physical and chemical variables have considerable impact on the biological life in a mountain river which include plankton, benthic algae, benthic invertebrate and finally the fishery resources. They are often subjected to extreme hydrological disturbances particularly during rainy seasons when increased volume of water create ’Wash Off" situation for existing fauna and flora. A case study of a lesser Himalayan river - the Gaula which drains the south-central part of Kumaon region in Uttaranchal is presented here. Since this river does not get snowmelt water, it mainly depends on steady flow of the groundwater round the year. The climate of the area is characterized with long winters, short summer and good amount of rain during monsoon months. The infiltrated groundwater which seeps into the surface soil layers during monsoon seasons is the chief source of discharge of water during winter and summer season. Keywords: Hydrobiology, flora and fauna, Himalayan river